PENGARUH PAJAK, UKURAN PERUSAHAAN, TUNNELING INCENTIVE, DEBT COVENANT, EXCHANGE RATE, DAN KEPEMILIKAN ASING TERHADAP KEPUTUSAN TRANSFER PRICING (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar Di BEI Pada Tahun 2014-2017) - Mandasari, Gusrina Putri; Zirman, Zirman; Rusli, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The purpose of this study is to obtain empirical evidence regarding the effect oftax, company size, tunneling incentive, debt covenant, exchange rate, and foreignownership of the company's transfer pricing decisions.The population in this study are allmanufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2017 period. Sampling method with purposive sampling technique, with samples thatmeet the criteria of 30 companies for 4 years, the total sample is 120 samples. Testing thehypothesis in this study using logistic regression with the support of SPSS 22 versionsoftware. The results of the study prove that (1) tax have an effect on transfer pricing at asignificance level of 0.016<0.050, (2) debt covenants have an effect on transfer pricing ata significance level of 0.046<0.050, and (3) an exchange rate have an effect on transferpricing at a significance level of 0.011<0,050, (4) company size has no effect on transferpricing at a significance level of 0.058>0.050, (5) tunneling incentive has no effect ontransfer pricing at a significance level of 0.284>0.050, and (6) foreign ownership has noeffect on transfer pricing with a significance level of 0.679>0.050.Keywords : Tax, Company Size, Tunneling Incentive, Debt Covenant, Exchange Rate,Foreign Ownership, Transfer Pricing